Responses to Offense at Work and the Impact of Hierarchical Status: The Fault of the Leader, Causal Attributions, and Social Support During the Covid-19 Pandemic Crisis - Marian, Mihai Ion; Barth, Karla Melinda; Oprea, Mihai Ionut (Frontiers in Psychology, 2021)
The study explores the mechanism by which unadapted causal attributions and the perception of social support stimulate revenge and reconciliation at the social and professional level in the context of the current pandemic. In particular, the purpose of the study is to investigate the relationship between the accused, the victim and offender status and the search for revenge or reconciliation following a personal offense. To test the suggested research model, we analysed the data collected by 167 (m=28.52; SD=8.98) employees in different organizations using a multifactorial experimental design. The results support the influence of attributional predictions in forming revenge and reconciliation and show that they are involved in the decision to carry out revenge, but especially in the way the employee interprets the trigger situation. In conclusion, the revenge is based on a negative attributional mechanism that produces the greatest deficit of adaptation to the situation and a weakening of the perception of social support, while reconciliation seems to be based on a much more complex socio-occupational mechanism. Leaders should pay attention to organizational communication during a crisis as they could encourage hopelessness depression. Adjusting crisis communication is crucial to ensuring job satisfaction that could mitigate negative effects.